A Cascadia Slab Model From Receiver Functions - Wasja Bloch; Michael G. Bostock; Pascal Audet (Geochemistry, Geophysics, Geosystems, 2023)
Abstract We map the characteristic signature of the subducting Juan de Fuca and Gorda plates along the entire Cascadia forearc from northern Vancouver Island, Canada, to Cape Mendocino in northern California, USA, using teleseismic receiver functions. The subducting oceanic crustal complex, possibly including subcreted material, is parameterized by three horizons capable of generating mode‐converted waves: a negative velocity contrast at the top of a low velocity zone underlain by two horizons representing positive contrasts. The amplitude of the conversions varies likely due to differences in composition and/or fluid content. We analyzed the slab signature for 298 long‐running land seismic stations, estimated the depth of the three interfaces through inverse modeling and fitted regularized spline surfaces through the station control points to construct a margin‐wide, double‐layered slab model. Crystalline terranes that act as the static backstop appear to form the major structural barrier that controls the slab morphology. Where the backstop recedes landward beneath the Olympic Peninsula and Cape Mendocino, the slab subducts sub‐horizontally, while the seaward‐protruding and thickened Siletz terrane beneath central Oregon causes steepening of the slab. A tight bend in slab morphology south of the Olympic Peninsula coincides with the location of recurring large intermediate depth earthquakes. The top‐to‐Moho thickness of the slab generally exceeds the thickness of the oceanic crust by 2–12 km, suggesting thickening of the slab or underplating of slab material to the overriding North American plate.